Recommendations for genetic testing and counselling after sudden cardiac death: practical aspects for Swiss practice (Swiss Medical Weekly, 2018)
There is a need to standardise, within a coordinated Swiss framework, the practical aspects of genetic testing and genetic counselling on possibly inherited cardiovascular disorders in relatives of a sudden cardiac death (SCD) victim. Because of the major advances in genetic investigation techniques and recent publication of international guidelines in the field of cardiology, genetics and pathology, we consider it important to summarise the current evidence and propose an optimal approach to post-mortem genetic investigation for SCD victims and their families in Switzerland. In this article, we discuss important technical, financial and medico-ethical aspects, and provide updated information on specific situations in which forensic pathologists, general practitioners and cardiologists should suspect a genetic origin of the SCD. At present, the principles of benefit, the duty to warn and the impact of genetic information for family members at risk are considered as strong justifications for post-mortem disclosure and prevail over the arguments of respect for a deceased person’s privacy and confidentiality. This paper underlines also the need to update and improve the general knowledge concerning the genetic risk of cardiovascular pathologies, the importance to perform an autopsy and post-mortem genetic testing in SCD victims, and to develop standardized post-mortem disclosure policy at national and international levels for SCD cases and relatives.